Effectiveness of an Emotional Intelligence Program in Elementary Education - Isabel Mª Merchán; Mª Luisa Bermejo; Juan de Dios González (Revista de Estudios e Investigación en Psicología y Educación, 2014)
The aim of this article is to demonstrate the positive effects of the implementation of a program to develop emotional competence in first year students of primary education. This population has been taking as public school students in the city of Badajoz during the course 2012-2013, selecting a sample of 78 pupils aged between 5 and 7 years, divided into experimental group and control group. The methodological procedure focuses on a descriptive-interpretative approach with two data collection techniques: sociometric test and test emotional intelligence. Designed and implemented a program of emotional intelligence with students in the experimental group, measured before and after the intervention the level of emotional competence and social relations of the class group. Similarly, measurements were taken of the degree of emotional competence and social relations of the students in the control group, which did not participate in the intervention. The results show that the program was effective to increase the emotional intelligence of students that make up the experimental group improved with it the degree of friendship and social relations of the class group.